Modern Leadership and Work Balance: Academic Supervision of Higher Education Performance - Arif Saefudin (Departement of Mathematics Education, 2024)
This study aims to determine the impact of transformational leadership, organizational culture, and work-life balance on the performance of lecturers and teaching staff, as regulated by academic supervision. Using an associative approach, the research sampled one hundred lecturers and utilized questionnaires and observations as research instruments. The findings reveal that academic supervision does not moderate the effect of transformational leadership on performance. However, it can moderate the effect of organizational culture on performance, while it does not moderate the effect of work-life balance on performance. This indicates that academic supervision does not entirely attenuate the impacts of transformational leadership, work-life balance, and organizational culture on the performance of lecturers at various tertiary institutions within LLDIKTI III. The implications of these findings are significant for the management and administration of tertiary institutions. Institutions should recognize that while academic supervision is a valuable tool for enhancing performance, its effectiveness is contingent upon the broader organizational context. Tailoring academic supervision practices to align with the specific cultural dynamics of the institution can maximize its positive impact on performance. Moreover, ensuring that lecturers maintain a healthy work-life balance is crucial for sustaining high performance, independent of supervisory practices.